Marine actinomycetes from Madeira Archipelago preliminary taxonomic studies - Rodrigues, Sara (2018)
Financial support from Fundação para a Ciência e a Tecnologia (FCT) and FEDER (through grant n° PTDC/QUI-QUI/119116/2010, and projects PEst-C/EQB/LA0006/2011 and Pest-OE/BIA/UI0457/2011-CREM), and the EU 7th Framework Programme (FP7/2007-2013) under grant agreement n° PCOFUND-GA-2009-246542 and nº 269138-NanoGuard. We thank W. Fenical, P. R. Jensen and C. A. Kauffman, from SIO, CA, USA and P. Castilho from Universidade da Madeira, Portugal for the logistic support during sampling collection.